Kinerja Dewan Perwakilan Rakyat Daerah dalam Rangka Perumusan Peraturan Daerah: Performance of the Regional People's Representative Council in the Formulation of Regional Regulations - Abdul Muis (Fenomena, 2009)
Post-1999 decentralization granted greater roles to Regional People's Representative Councils (DPRD), yet the executive's dominance in local legislation remains strong. This study evaluates the performance of Jember Regency's DPRD in exercising legislative, oversight, and budgetary functions, particularly in formulating regional regulations. Using a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation of DPRD members, secretariat staff, and official documents from the 1999-2004 period. Findings reveal that although member attendance exceeded 90% and discussion creativity was relatively high, the DPRD's initiative in proposing draft regional regulations was very low, with only 5 out of 205 regional regulations (2.44%) originating from the council. Most regulations were executive-initiated, particularly concerning organizational structures and procedures. Key constraints include low human resource quality among members, complicated mechanisms for exercising initiative rights, and executive dominance. The study concludes that legislative productivity is not matched by adequate legislative initiative, necessitating capacity building for members and simplification of the initiative mechanism for draft regional regulations. Desentralisasi pasca-1999 memberikan peran besar kepada DPRD, namun realitas menunjukkan dominasi eksekutif dalam legislasi daerah masih kuat. Penelitian ini bertujuan mengevaluasi kinerja DPRD Kabupaten Jember dalam menjalankan fungsi legislasi, pengawasan, dan anggaran, khususnya dalam perumusan Peraturan Daerah. Dengan pendekatan deskriptif kualitatif, data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi terhadap anggota DPRD, sekretariat, serta dokumen resmi periode 1999-2004. Hasil penelitian menunjukkan bahwa meskipun tingkat kehadiran anggota di atas 90% dan kreativitas dalam pembahasan cukup tinggi, inisiatif DPRD dalam mengusulkan Raperda sangat rendah, yaitu hanya 5 dari 205 Perda (2,44%) yang merupakan prakarsa DPRD. Sebagian besar Perda justru berasal dari eksekutif, terutama menyangkut struktur organisasi dan tata kerja. Kendala utama meliputi rendahnya kualitas sumber daya manusia anggota, mekanisme pengajuan hak inisiatif yang rumit, serta dominasi eksekutif. Penelitian ini menyimpulkan bahwa produktivitas legislasi belum diikuti oleh inisiatif legislatif yang memadai, sehingga diperlukan peningkatan kapasitas anggota dan penyederhanaan mekanisme pengajuan Raperda inisiatif DPRD.